Influência dos polimorfismos nos genes das citocinas TNFα, IFNγ, TGFβ, IL-6 E IL-10 no perfil clínico-laboratorial de pacientes com anemia falciforme - Cavalcante, Janio Emanuel Andrade (2013)
Sickle cell anemia (SCA) is caused by a point mutation leading the substitution of glutamic acid for valine at the sixth position of the beta globin chain. Associations between single nucleotide polymorphisms (SNPs) and several clinical events have been described in sickle cell patients. The aim of this study was to determine the polymorphisms frequency in the cytokine genes TNFα, IFNγ, TGFβ, IL-6 e IL-10 in sickle cell patients and healthy controls, and to investigate the cytokines genotypes influence in clinical and laboratory profile in sickle cell patients. The sickle cell patients group was composed by 41 adults’ patients with molecular diagnosis, of both sexes, in outpatients care at the Hematology Center of Ceará (HEMOCE), from march 2011 to july 2012. The study included 90 healthy blood donors matched for age and sex. We collected 5 mL of venous blood for DNA extraction kit using the GFX Genomic Blood DNA Purification (GE Healthcare) and typing of cytokine genes polymorphisms by kit from One-Lambda (Canoga Park, CA, USA). The polymorphisms frequencies analysis and associations between polymorphisms and clinical events were performed using the two-tailed Fisher exact test. To check the genotypes influence in laboratory parameters were used parametric test ANOVA and non-parametric Kruscal Wallis test. The clinical and laboratory data were obtained by active search in the medical records. Sickle cell patients typified for TGFβ genotypes showed a tendency to appear a lower frequency of TGFβ T/T G/G genotype than control group. Sickle cell patients typified for CC GC/ CC CC /TT CC/TC CC TGFβ genotypes (low producer) obtained a leukocytes median number greater than patients typified for TT GG/TC GG TGFβ group (high producer). A significant difference on IL-6 genotypes frequency was observed between patient group and control group. Regarding IL-6, patients typified for CC genotype exhibited an average/median MCHC higher than patients typified for GC or GG genotypes. Patients typified for CC genotype showed evident tendency to lower fetal hemoglobin levels and higher reticulocytes percentages. We find an association between ACC ATA + ATA ATA + ACC ACC IL-10 group, lower IL-10 producer, and acute chest syndrome (ACS). It is concluded that genotypes associated with low IL-10 production may play a role in the predisposition to ACS in sickle cell patients.